Assessing the impact of digital transformation dimensions on the development of social security services: Case study of the National Fund for Social Insurance for Workers in the State of Constantine - MAZOUZ, Samia (Journal of Human Sciences, 2025)
This research seeks to examine how digital transformation influences the advancement and enhancement of social security services. , where the analytical descriptive curriculum was adopted .To fulfill the research objectives, a questionnaire was distributed to a sample of 52 employees working at the National Social Insurance Fund in the province of Constantine. Statistical analysis was also carried out using SPSS 27 software.  The study produced several results, notably a statistically significant moral link between human resources skills and the development of the Fund's services. The availability of the necessary technologies and infrastructure has been shown to have a positive and statistically significant impact on the improvement of these services.,in addition, the findings showed that the Fund’s management follows an efficient method of data management, which has played a significant role in streamlining many processes.